2016
DOI: 10.1177/0271678x15622463
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal myosin phosphatase targeting subunit 1 phosphorylation and actin polymerization contribute to impaired myogenic regulation of cerebral arterial diameter in the type 2 diabetic Goto-Kakizaki rat

Abstract: The myogenic response of cerebral resistance arterial smooth muscle to intraluminal pressure elevation is a key physiological mechanism regulating blood flow to the brain. Rho-associated kinase plays a critical role in the myogenic response by activating Ca sensitization mechanisms: (i) Rho-associated kinase inhibits myosin light chain phosphatase by phosphorylating its targeting subunit myosin phosphatase targeting subunit 1 (at T855), augmenting 20 kDa myosin regulatory light chain (LC) phosphorylation and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
(128 reference statements)
1
18
0
Order By: Relevance
“…This transition from compensatory increases in myogenic tone to autoregulatory failure has been observed in the type 2 diabetic Goto-Kakizaki rat, in that exaggerated pressure-induced contraction precedes loss of myogenic responses with ageing. 3234 Impaired myogenic reactivity contributes to renal injury in the Dahl salt-sensitive rat 35 , whereas enhanced myogenic contractions and preserved renal function are found in the spontaneously hypertensive rat. 28 Similarly, in diabetic patients, loss of myogenic control is associated with the development of retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…This transition from compensatory increases in myogenic tone to autoregulatory failure has been observed in the type 2 diabetic Goto-Kakizaki rat, in that exaggerated pressure-induced contraction precedes loss of myogenic responses with ageing. 3234 Impaired myogenic reactivity contributes to renal injury in the Dahl salt-sensitive rat 35 , whereas enhanced myogenic contractions and preserved renal function are found in the spontaneously hypertensive rat. 28 Similarly, in diabetic patients, loss of myogenic control is associated with the development of retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Abd-Elrahman et al reported that cerebral arteries isolated from T2D diabetic rats experienced an increased basal myogenic tone at low pressure points (1). They demonstrated that increased basal Rho-associated protein kinase (ROCK2) activity was responsible for the observed elevation in myogenic tone via inhibiting MLCP as well as mediating actin polymerization.…”
Section: Autoregulation and Myogenic Behaviormentioning
confidence: 99%
“…Although reduced myogenic constriction was reported in GK rats ( Kold-Petersen et al, 2012 ), longitudinal studies in cerebral arterioles of this model provided the molecular basis for the progressive loss of myogenic response from the prediabetic to the diabetic stage. Cerebral arterioles from these rats demonstrated an enhanced myogenic behavior during the prediabetic phase ( Abd-Elrahman et al, 2015a ). Specifically, enhanced LC20 phosphorylation and increased actin polymerization (lower G-actin level) occurred at low intraluminal pressure due to an increase in ROK activity rather than ROK protein expression.…”
Section: Alterations In Rok Activity In Pathological Conditionsmentioning
confidence: 99%